Dutch Harbor waterfront showing manager's residence, hotel and store of the North American Commercial Company, Amaknak Island in Unalaska, Alaska, probably 1899 - Warner, Arthur Churchill, 1864-1943 (1899)
On verso of image: Unalaska Warner [2018] Filed in Alaska series. The North American Commercial Co. was first incorporated in 1889. The company had a coaling station at Dutch Harbor. In 1890 it acquired exclusive rights to harvest fur seals on the islands of St. George and St. Paul in the Pribilof Islands from the U.S. Government.